Fast Acquisition of Heart Rate in Noncontact Vital Sign Radar Measurement Using Time-Window-Variation Technique - Tu, Jianxuan; Lin, Jenshan (IEEE transactions on instrumentation and measurement, 2016)
The fast acquisition of heart rate (HR) is a challenge in noncontact vital sign detection using a Doppler radar system. Most of the previous studies use long-period time windows to guarantee a sufficient frequency spectrum resolution for HR measurement using the peak searching method on the frequency spectrum. For fast acquisition of HR, the length of the time window is less than 5 s and the accuracy is significantly degraded due to insufficient spectrum resolution. For vital sign detection using complex signal demodulation (CSD), measuring HR variation becomes a difficult job due to respiration harmonic interference and insufficient frequency spectrum resolution. In this paper, a time-window-variation technique is developed for fast acquisition of HR from short-period time windows and measuring HR variation using CSD. Experiments are performed on four human subjects under controlled laboratory conditions by a 5.8-GHz continuous-wave Doppler radar vital sign detection system. The HR measurement results within 2-5-s time windows are compared by applying a simple fast Fourier transform (FFT) and peak searching method, a 10-s sliding-time-window FFT method, and the proposed method. The proposed method achieves the smallest average error among the three techniques. The proposed method has also proved to be able to measure HR variation using CSD.